2022
DOI: 10.1021/acs.est.1c08096
|View full text |Cite
|
Sign up to set email alerts
|

Alkali and Heavy Metal Copoisoning Resistant Catalytic Reduction of NOx via Liberating Lewis Acid Sites

Abstract: The catalyst deactivation caused by the coexistence of alkali and heavy metals remains an obstacle for selective catalytic reduction of NOx with NH3. Moreover, the copoisoning mechanism of alkali and heavy metals is still unclear. Herein, the copoisoning mechanism of K and Cd was revealed from the adsorption and variation of reaction intermediates at a molecular level through time-resolved in situ spectroscopy combined with theoretical calculations. The alkali metal K mainly decreased the adsorption of NH3 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Among them, the peaks located at 1004, 1186 cm −1 (CuO x /CeO 2 -H), 1001, 1189 cm −1 (CuO x /CeO 2 -T), 1180, 1619 cm −1 (CuO x /CeO 2 -C) and 1604, 1189 cm −1 (CuO x /CeO 2 -F) are attributed to the vibration modes of bridging bidentate nitrates. 50,51,53–56 The bands at 1552 cm −1 (CuO x /CeO 2 -H), 1567 cm −1 (CuO x /CeO 2 -T) and 1556 cm −1 (CuO x /CeO 2 -C) can be assigned to the chelating bidentate nitrates. The bands at 1366 cm −1 (CuO x /CeO 2 -T) 1399 cm −1 (CuO x /CeO 2 -C) correspond to the free NO 3 − .…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the peaks located at 1004, 1186 cm −1 (CuO x /CeO 2 -H), 1001, 1189 cm −1 (CuO x /CeO 2 -T), 1180, 1619 cm −1 (CuO x /CeO 2 -C) and 1604, 1189 cm −1 (CuO x /CeO 2 -F) are attributed to the vibration modes of bridging bidentate nitrates. 50,51,53–56 The bands at 1552 cm −1 (CuO x /CeO 2 -H), 1567 cm −1 (CuO x /CeO 2 -T) and 1556 cm −1 (CuO x /CeO 2 -C) can be assigned to the chelating bidentate nitrates. The bands at 1366 cm −1 (CuO x /CeO 2 -T) 1399 cm −1 (CuO x /CeO 2 -C) correspond to the free NO 3 − .…”
Section: Resultsmentioning
confidence: 99%
“…Selective catalytic reduction of NO x with ammonia (NH 3 -SCR) is considered an effective method to remove NO x . Herein, V 2 O 5 -WO 3 /TiO 2 catalysts have been commercially used for industrial and mobile sources. Currently, in addition to the toxicity of vanadium, SCR catalysts face considerable deactivation by alkali metals in the flue gas in practical applications, especially for alkali-rich stack gases such as power plants fueled by biomass. It has been observed that the physical poisoning of alkali metals on vanadia-based catalysts blocks the pore structures and harshly affects reactant diffusion. Conversely, chemical poisoning is caused by the reduction of Brønsted acidity. , …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported that the dopant of Boron effectively relieved the poisoning effect of CeO 2 /TiO 2 catalysts for alkali resistance. Shen et al . found that acid additives could maintain the alkali-resistant ability of CeO 2 /TiO 2 catalysts and further relieve SCR catalyst poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, selective catalytic reduction (SCR) of NO x with ammonia is generally recognized as the most efficient technology for reducing the abatement of NO x [8–10] . The commercial V 2 O 5 ‐WO 3 /TiO 2 catalysts have widespread application in coal‐fired power plants because of the satisfactory SCR activity in temperature of 300–400 °C [11,12] . However, the commercial V 2 O 5 based catalysts are not efficient for some applications, like steel and cement production, and nonelectrical industries, in which the flue gas temperatures are always below 300 °C.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The commercial V 2 O 5 -WO 3 / TiO 2 catalysts have widespread application in coal-fired power plants because of the satisfactory SCR activity in temperature of 300-400 °C. [11,12] However, the commercial V 2 O 5 based catalysts are not efficient for some applications, like steel and cement production, and nonelectrical industries, in which the flue gas temperatures are always below 300 °C. Particularly, alkali/ alkaline metals in flue gas could severely deactivate catalysts due to the loss of surface acidity and redox ability.…”
Section: Introductionmentioning
confidence: 99%